Current and emerging pharmacological treatments for sarcoidosis: a review - Beegle SH; Barba K; Gobunsuy R; Judson MA (Dove Medical Press, 2013)
Scott H Beegle,1 Kerry Barba,2 Romel Gobunsuy,1 Marc A Judson1 1Division of Pulmonary and Critical Care Medicine, 2Department of Medicine, Albany Medical College, Albany, NY, USA Abstract: The treatment of sarcoidosis is not standardized. Because sarcoidosis may never cause significant symptoms or organ dysfunction, treatment is not mandatory. When treatment is indicated, oral corticosteroids are usually recommended because they are highly likely to be effective in a relative short period of time. However, because sarcoidosis is often a chronic condition, long-term treatment with corticosteroids may cause significant toxicity. Therefore, corticosteroid sparing agents are often indicated in patients requiring chronic therapy. This review outlines the indications for treatment, corticosteroid treatment, and corticosteroid sparing treatments for sarcoidosis. Keywords: pulmonary sarcoidosis, extrapulmonary sarcoidosis, treatment, drugs, corticosteroids